Hydrate deposition prediction model for deep-water gas wells under shut-in conditions. (1st September 2020) - Wang, Zhiyuan; Tong, Shikun; Wang, Chao; Zhang, Jianbo; Fu, Weiqi; Sun, Baojiang
Highlights: A model is proposed to predict the hydrate deposition for deep-water gas wells under shut-in condition. The deep-water wellbore environment after shut-in is divided into transient stage and steady stage. The hydrate formation region and thickness distribution at different shut-in time can be analyzed by the model. This work is beneficial to optimize conventional strategy of hydrate management under shut-in conditions. Abstract: Natural gas hydrate is one of the major issues in the development of deep-water oil and gas industry. The shut-in operation increases the risk of hydrate formation under higher pressure and lower temperature conditions. Conventional hydrate prevention methods may inject excessive amount of inhibitors, which leads to additional cost and environmental pollution. There are few studies on quantitative prediction of hydrate formation and deposition after deep-water shut-in. In this paper, a prediction model of hydrate deposition considering water vapor condensation and liquefaction for deep-water gas well under shut-in conditions is established. The deposition model is divided into transient and steady stage based on the variation characteristics of temperature. During the process of hydrate formation after shut-in operation, the consumption amount of free water is used as the verification parameter in this paper, and the average error between the experimental results and the simulations is 11.75%. The simulations suggest that the amount of hydrate deposition will increase as the shut-in time increase and the initial temperature raise along with the change of production parameters, but the overall deposition amount is small. Furthermore, especially in the short-term shut-in operations for deep-water gas wells, the low rate of water vapor diffusion and liquidation causes a small amount of deposited hydrate, which is not serious enough to cause blockage issues. The simulation results changed the conventional prevention recognition and it is helpful to decrease the cost of hydrate management. This study can serve as useful suggestions for the design and optimization for deep-water gas wells under shut-in conditions.